2020
DOI: 10.1016/j.jss.2020.110570
|View full text |Cite
|
Sign up to set email alerts
|

Software-testing education: A systematic literature mapping

Abstract: Context: With the rising complexity and scale of software systems, there is an ever-increasing demand for sophisticated and cost-effective software testing. To meet such a demand, there is a need for a highly-skilled software testing work-force (test engineers) in the industry. To address that need, many university educators worldwide have included software-testing education in their software engineering (SE) or computer science (CS) programs. Many papers have been published in the last three decades (as early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 81 publications
0
15
0
1
Order By: Relevance
“…At this stage the system testing will be carried out to ensure that the system being developed is running according to its functionality [29], testing this system using blackbox testing as a means of validating existing functionality [30], blackbox testing is internal testing at the development stage, so testing is carried out by internal developers until the feature runs according to the expected results. Blackbox testing results can be seen in Table 3.…”
Section: System Testingmentioning
confidence: 99%
“…At this stage the system testing will be carried out to ensure that the system being developed is running according to its functionality [29], testing this system using blackbox testing as a means of validating existing functionality [30], blackbox testing is internal testing at the development stage, so testing is carried out by internal developers until the feature runs according to the expected results. Blackbox testing results can be seen in Table 3.…”
Section: System Testingmentioning
confidence: 99%
“…O método utilizado neste estudo foi o mapeamento sistemático [Kitchenham et al 2010, Petersen et al 2008. Embora existam estudos sobre o ensino de teste de software [Valle et al 2015, Garousi et al 2020] e ensino de programação integrado ao teste de software [Scatalon et al 2017, Scatalon et al 2019, não pudemos identificar trabalhos que contemplem TDD ou teste de software especificamente quantoà resolução de problemas. Desta forma, o mapeamento sistemático foi realizado, sendo organizado em duas iterações.…”
Section: Métodounclassified
“…However, it has created new challenges, such as the cost of the approach and the lack of empirical data, to examine its benefits along with the lack of unified steps for educators in SE [12]. Based on a recent systematic review, Garousi et al have categorized the obstacles during adopting different methods of teaching software testing into challenges related to instructors and students as well as the challenges related to instructors [13]. Within the first category, the authors have identified three challenges, which are low motivation, learning new tools, and the need to increase cognitive load of students.…”
Section: B Online-learn Software Engineeringmentioning
confidence: 99%
“…Online teaching of SE adds the aforementioned challenges into the main challenges being faced while adopting pedagogical online teaching approach. Though online teaching pave the way for SE educators to enhance the utilization of new teaching methods over traditional ones that are time consuming and do not allow instructors to fully teach concepts during the class time, such as the tools for software testing education [13]. For example, it has been found that most of the courses that are taught using non-traditional pedagogical approaches, such as online and blended courses, and adopted the gamerelated approach in SE education have utilized the approach completely during the online part [12].…”
Section: B Online-learn Software Engineeringmentioning
confidence: 99%